ANALYSIS OF TENSILE STRENGTH IN GTAW WITH WELDING CURRENT AND TUNGSTEN DIAMETER VARIATIONS ON ST-37 STEEL - Ichlas Wahid; Maula Nafi; Ronny Wahyu Wantara; Imah Luluk Kusminah (International Conference of Innovation and Community Engagement, 2025)
Gas Tungsten Arc Welding (GTAW) is commonly used in construction due to its precision and efficiency. This research focuses on assessing the tensile strength of ST 37 steel welded using GTAW with different tungsten electrode diameters and current settings. The electrode sizes used were 1.6 mm, 2.4 mm, and 3.2 mm, paired with current levels of 60 A, 80 A, and 100 A. Tensile strength testing was performed following ASTM E8 standards. The results indicated that the 3.2 mm electrode with 100 A current produced the highest tensile strength at 43.13 kg/mm², while the 1.6 mm electrode with 60 A current yielded the lowest tensile strength at 29.75 kg/mm². These findings demonstrate that higher current levels in GTAW welding result in greater tensile strength for ST 37 steel, offering valuable guidance for optimizing welding parameters in industrial settings